2002
DOI: 10.1182/blood.100.7.2668
|View full text |Cite
|
Sign up to set email alerts
|

Phagocytosing neutrophils down-regulate the expression of chemokine receptors CXCR1 and CXCR2

Abstract: IntroductionTwo major responses are central to neutrophil leukocyte (polymorphonuclear neutrophil [PMN]) functioning: chemotaxis and phagocytosis. The migration of leukocytes is governed by chemotactic cytokines called chemokines. Chemokines are a large family of small chemotactic proteins divided into 4 subfamilies according to the positioning of cysteines in their primary sequences. Those whose first 2 cysteines are separated by one amino acid belong to the CXC (or ␣) subfamily and regulate the responses of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
24
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 21 publications
3
24
1
Order By: Relevance
“…Downregulation of chemokine receptors aids retention of PMN at sites of infection, and bacterial phagocytosis has been shown to promote this downregulation (24). A reduced migratory response of diabetic PMN toward IL-8 has been demonstrated in vitro (11) and is supported by the differences observed in CD11b expression on PMN from PC-T2D and ND individuals in the present study.…”
Section: Discussionsupporting
confidence: 76%
“…Downregulation of chemokine receptors aids retention of PMN at sites of infection, and bacterial phagocytosis has been shown to promote this downregulation (24). A reduced migratory response of diabetic PMN toward IL-8 has been demonstrated in vitro (11) and is supported by the differences observed in CD11b expression on PMN from PC-T2D and ND individuals in the present study.…”
Section: Discussionsupporting
confidence: 76%
“…2 and 4). Inasmuch as previous studies indicate that phagocytosis per se reduces surface expression of both receptors (20), it is likely that down-regulation of CXCR1 and CXCR2 early after phagocytosis of pathogens (within 90 min) is not regulated at the level of gene expression, an idea supported by our findings (see gene expression at 90 min). However, significantly reduced expression of genes encoding CXCR1 and CXCR2 at much later times after phagocytosis (e.g., at 3 and 6 h) likely contributes to the continued absence of expression of these receptors on the surface of human PMNs (Fig.…”
Section: Confirmation Of Microarray Data By Taqman Real-time Rt-pcr Andsupporting
confidence: 85%
“…Thus, it is logical to suppose that TLRs might down-modulate neutrophil trafficking to keep these cells at the site of infection. Indeed, it has been shown that bacteria phagocytosis results in decreased surface expression of CXCR1 and CXCR2 in human neutrophils (21,22). Extrapolating to a systemic infection context with high blood levels of TLR agonists, the down-regulation of chemokine receptors in peripheral circulating neutrophils (''wrong compartment'') may explain the drastic reduction of these cells in the infection focus.…”
Section: Discussionmentioning
confidence: 99%